2022
DOI: 10.1186/s13047-022-00567-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and experiences towards the application of motivational interviewing by podiatrists working with people with diabetes at high‐risk of developing foot ulcers: a mixed‐methods study

Abstract: Background Podiatrists are key professionals in promoting adequate foot self-care for people with diabetes at high-risk of developing foot ulcers. However, merely informing patients about the advantages of foot self-care is insufficient to realise behavioural change. Motivational interviewing (MI) is a promising person-centred communication style that could help to create a working alliance between healthcare providers and patient to improve foot self-care. This study aims to observe and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Other previous studies showed that someone's decision to use orthopaedic footwear can be influenced by the communication style of the healthcare provider, which is associated with increased long-term footwear usefootwear [7,31]. However, adequately powered randomized controlled trials are needed to establish the efficacy of communication styles in improving adherence to wearing orthopaedic shoes [32][33][34]. Therefore, to determine patients' adherence to wearing orthopaedic footwear in daily practice it should be objectively measured on an individual level rather than estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies showed that someone's decision to use orthopaedic footwear can be influenced by the communication style of the healthcare provider, which is associated with increased long-term footwear usefootwear [7,31]. However, adequately powered randomized controlled trials are needed to establish the efficacy of communication styles in improving adherence to wearing orthopaedic shoes [32][33][34]. Therefore, to determine patients' adherence to wearing orthopaedic footwear in daily practice it should be objectively measured on an individual level rather than estimated.…”
Section: Discussionmentioning
confidence: 99%